Genetic Variation of Trees of Caryocar brasiliense for Fruit Morphometric Traits - Hernandez, Liliana Hernandez; Santos, Fabio Araujo dos [UNESP]; Palomino, Edwin Camacho; Tambarussi, Evandro Vagner; Moraes, Cristiano Bueno (Univ Federal Rural Rio De Janeiro, Inst Florestas, 2021)
This study aimed to verify the genetic variability of matrix trees of Caryocar brasiliense, best known by the popular name of pequi, in a completely random delineation, with 20 treatments (matrices), and 50 repetitions (collected fruits in each matrix). We have evaluated the following traits of each fruit: weight (g), diameter (cm), length (cm), width (cm), and thickness (cm). As results we obtained a coefficient of experimental variation (CVe(%)) that showed advantageous values of 2.82 to 7.80, and the genotype heritability ((h(g)(2) (%)) of 55 to 95; both results can indicate favorable genetic control in the traits of the fruit. At the same time certain traits have significant genotypic and phenotypic correlations, which can be understood as an advantage for the improvement of the specie. In conclusion, we have noted that the population of Caryocar brasiliense has a high genetic variation, these results support the planning for genetic improvement programs.
Keywords: pre-breeding; genetic variability; fruit; pequi; Cerrado